A research model of inclusiveness - Varga, Aranka (Autonomy and Responsibility Journal of Educational Sciences, 2022)
The present contribution aims at providing a process-level interpretation of inclusion, as a theoretical framework in order to make it adaptable for the analysis of practical everyday actions from the viewpoint of equity. Building on the foundation of the approach characterized by equal opportunities, and with the presentation of several educational models of inclusion we summarize the input criteria of realizing mutual inclusion, the necessary conditions of maintaining inclusion and the characteristics of successful realization at different points of the inclusive process. Through this synthetizing piece of work we intend to set the course for further steps that may tackle the issues of structural requirements for embedding inclusion, horizons of content and frameworks for society-level actions.